The Effect Of Physical Effort Using Different Temperatures On Youth Soccer Players' Hemoglobin - Hanoon, Wesam; Mohi, Rassol (Journal of Physical Education, 2016)
The aim of the research was to identify the effect of physical effort usingdifferent temperatures on one blood variable (hemoglobin) for youth soccer players. Theresearchers hypothesized statistical difference in physical effort on hemoglobin of youthsoccer players. The researchers used the descriptive method on 13 soccer players. The resultsshowed that the highest hemoglobin level was at 45degree after effort reaching 15.185 gram.